Effect of conservation agriculture and nitrogen management on root architecture and soil properties in maize–wheat cropping system - CHOUDHARY, R.L.; BEHERA, U.K. (Journal of Soil and Water Conservation, 2020)
A field experiment was conducted to evaluate the effect of conservation agricultural and nitrogen management practices on root architecture and soil physical, chemical and biological properties after 2- years of continuous maize–wheat cropping system. The experiment was carried out in split plot design with six main plot treatments of tillage and crop establishment techniques, i.e. conventional tillage-flat bed (CT-F), CT-raised bed (CT-B), zero tillage-flat bed with crop residue (ZT-F+R) and without crop residue (ZT-F), ZT-raised bed with crop residue (ZT-B+R) and without crop residue (ZT-B) and four sub plot treatments of nitrogen (N), i.e. 0, 60, 120 and 180 kg N ha-1. Most of the soil physical, chemical and biological parameters were significantly improved with ZT-B+R as compared to other treatments. ZTB+ R recorded 7.7 and 9.1% higher organic carbon than CT-B and CT-F, respectively. Microbial biomass carbon, dehydrogenase activity and fluorescein diacetate hydrolysis were improved by 57.4, 47.0 and 55.4% with ZT-B+R over CT-F, respectively. ZT-B+R also registered significantly lower bulk density compared to ZT without residue and CT-F treatments. The same treatment also improved the aggregation, hydraulic conductivity, infiltration rate and available N, P and K in soil. Root length density (RLD), root surface area (RSA) and root volume density (RVD) of maize and wheat were also recorded higher with ZT-B+R which was at par with CT-B and ZT-B, but significantly higher than CT-F and ZT-F treatments. Nitrogen levels did not exert significant influence on most of the soil properties, however, organic carbon and biological activities in soil improved up to 60 kg N ha-1, while soil available N, RLD, RSA and RVD improved significantly up to 120 kg N ha-1. Thus, we concluded that permanent-bed with crop residue (ZT-B+R) and 120 kg N ha-1 was found to be beneficial for improving soil health and root growth of maize and wheat crops.